Development and characterization of in vitro self-assembled recombinant human follicle stimulating hormone originated from goat mammary epithelial cells. (15th April 2021) - Hua, Rongmao; Cheng, Jianyong; Yang, Li; Zhang, Zelin; Xu, Dejun; Chen, Huali; Li, Yuan; Duan, Jiaxin; Li, Xiaoya; Geng, Guoxia; Liu, Jianxi; Li, Qingwang
Abstract: Follicle stimulating hormone (FSH), composed of FSHα and FSHβ subunits, is essential for female follicle development and male spermatogenesis. The recombinant human FSH (rhFSH) products on the market are mainly generated from mammalian cells and are expensive. Large animal mammary gland bioreactors are urgently needed to produce large amounts of rhFSH. However, there are currently no effective methods to prepare rhFSH by large animals mainly due to the fact that excessive accumulation of FSH might cause many adverse effects in animals. We herein report the development and characterization of functional self-assembled rhFSH produced in goat mammary epithelial cells (GMECs). FSHα and FSHβ stably expressed in Chinese hamster ovary (CHO) cell lines were secreted into culture medium and well glycosylated. Importantly, FSHα and FSHβ expressed apart were able to assemble into functional FSH. We next inserted human FSHα or FSHβ gene separately into goat β-Lactoglobulin locus in GMECs by CRISPR/Cas9. Inactive FSHα and FSHβ subunits expressed from GMECs assembled into rhFSH as analyzed by His-tag pull down assay. Functional assessment of rhFSH by cAMP induction assay, mouse ovulation induction and rat ovarian weight gain experiments showed that the bioactivity of self-assembled rhFSH expressed by GMECs was comparable to that of Gonal-F both in vitro and in vivo. Our study demonstrated that FSHα and FSHβ can be separately expressed and assembled into functional rhFSH, and provided the basis for future preparing FSH by goat mammary gland bioreactor with less health problems on the producing animals. Highlights: Human FSHα and FSHβ were individually integrated into the genome of mammary gland expression loci. Separately expressed subunit proteins were secretable and well glycosylated. FSHα and FSHβ expressed apart reassemble at 4 °C to form intact recombinant human FSH. Recombinant human FSH has potent bioactivity both in vitro and in vivo.